Delayed Postoperative Epidural Hematoma Presenting Only with Vesicorectal Disturbance. (29th August 2013) - Kamoda, Hiroto; Ishikawa, Tetsuhiro; Miyagi, Masayuki; Eguchi, Yawara; Orita, Sumihisa; Suzuki, Miyako; Sakuma, Yoshihiro; Oikawa, Yasuhiro; Yamauchi, Kazuyo; Inoue, Gen; Takahashi, Kazuhisa; Ohtori, Seiji
Abstract : We present a rare case of delayed onset of epidural hematoma after lumbar surgery whose only presenting symptom was vesicorectal disturbance. A 68-year-old man with degenerative spinal stenosis underwent lumbar decompression and instrumented posterolateral spine fusion. The day after his discharge following an unremarkable postoperative course, he presented to the emergency room complaining of difficulty in urination. An MRI revealed an epidural fluid collection causing compression of the thecal sac. The fluid was evacuated, revealing a postoperative hematoma. After removal of the hematoma, his symptoms disappeared immediately, and his urinary function completely recovered. Most reports have characterized postoperative epidural hematoma as occurring early after operation and accompanied with neurological deficits. But it can happen even two weeks after spinal surgery with no pain. Surgeons thus may need to follow up patients for at least a few weeks because some complications, such as epidural hematomas, could take that long to manifest themselves.